Influence of technological parameters on the properties of sol-gel silica films - Karasiński, Paweł (Oficyna Wydawnicza Politechniki Wrocławskiej, 2005)
The paper presents the influence of selected technological parameters on the properties of silica films produced in sol-gel processes using the dip-coating method. The influence of water content and catalyst content was investigated as well as the influence of aging time of sols. It was demonstrated that the conditions of film deposition and the content of catalyst have a great influence on the thickness of the films produced. The greatest influence on the refractive index is exerted by molar ratio TEOS:H2O. Together with the rise of aging time of the sol its properties are changing, and the changes depend on pH.
Optica Applicata, Vol. 35, 2005, nr 1, s. 117-128
Keywords: optyka; sol-gel; silica film; dip coating